New Conjugatable Platinum(II) Chlorins: Synthesis, Reactivity and Singlet Oxygen Generation - José Almeida; Giampaolo Barone; Luís Cunha-Silva; Ana F. R. Cerqueira; Augusto C. Tomé; Maria Rangel; Ana M. G. Silva (Molecules, 2025)
An efficient protocol was developed for the microwave-mediated metallation of 5-(4-methoxycarbonylphenyl)-10,15,20-tris(pentafluorophenyl)porphyrin (P1) with bis(benzonitrile)platinum dichloride salt and subsequent 1,3-dipolar cycloaddition of the resulting PtP1 with an azomethine ylide to give two isomeric metallochlorins: PtC1 (main isomer) and PtC3. The methyl ester group of metalloporphyrin PtP1 and metallochlorin PtC1 was successfully hydrolysed in an alkaline medium to yield the corresponding derivatives PtP2 and PtC2 in moderate-to-good yields. As a proof of concept of the reactivity of the carboxy group in PtP2 and PtC2, these compounds were conjugated with a hydroxylated derivative of indomethacin, a known potent non-steroidal anti-inflammatory, obtaining the conjugates PtP2-Ind and PtC2-Ind. The obtained platinum(II) porphyrins and chlorins were characterized by UV-Vis, NMR spectroscopy and mass spectrometry. The structure of PtP1 was also confirmed by X-ray crystallography. Singlet oxygen generation studies were carried out, as well as theoretical calculations, which demonstrated that the prepared Pt(II) complexes can be considered potential photosensitizers for PDT.